A Practical Research on the Development of an Information Technology School-Based Curriculum for Cultivating Computational Thinking Skills in Lower-Grade Primary School Students: Taking Graphical Programming Enlightenment Education in After-School Services as an Example - Tan Ying (Education Research on Study Tours and Practice, 2025)
In light of the increasing demands for students’ abilities under the trend of artificial intelligence and innovative development, cultivating students’ computational thinking skills is the teaching objective of the information technology subject in primary schools. Due to their strong visual cognitive thinking, lower-grade primary school students can better meet this characteristic with graphical programming, which has considerable room for development in teaching applications. However, in the current primary and secondary school field, most of the research on curriculum development is for upper-grade and above students. The implementation of theoretical and practical courses for lower-grade students still needs to be continuously improved. Based on this, we take the lower grades of primary school as the main object, develop the school-based information technology curriculum by combining the application scenarios of after-school services, and design the practical route of its graphical programming enlightenment education method. Eventually, a computational thinking cultivation model for the lower grades of primary school is formed. The research results can provide targeted reference plans for the teaching work of information technology teachers in the primary school stage, which is conducive to extending the cultivation of computational thinking to the lower grades of primary school.